RANCANG BANGUN SISTEM PENGENDALI KURSI RODA LISTRIK PENYANDANG DISABILITAS BERBASIS MIKROKONTROLER ARDUINO UNO ATmega 328P - Sabeilai, Jilva Krisye; Susilo, Susilo; Widodo, Bambang (Lektrokom : Jurnal Ilmiah Teknik Elektro, 2024)
For people with physical impairments, wheelchairs are the tools that are most widely used in their activities and are also the most widely used in hospitals. There are two types of wheelchairs that are often used, namely manual wheelchairs and electric wheelchairs. The electric wheelchair is designed using an Arduino Uno microcontroller, a set of buttons, and a motor driver circuit. Using the Arduino Uno as a microcontroller makes the system cost-effective and easy to access. Electric wheelchairs can move on a flat track using a pushbutton, which means the wheelchair can be moved easily. This research also uses the Arduino uno ATmega 328P as a wheelchair controller which is modified into two types, namely fast and slow according to the motor and battery capabilities. The performance test on this wheelchair includes the ability to lift loads with a maximum weight of 18 kg and subjects with an age range of 21 to 26 years with a maximum subject weight of 65 kg. From the test results, the wheelchair with a load of 11-18kg can move around 1.00 – 10.84 s. test results with subjects weighing 49-66kg moving around 1.00 – 8.00 s for each different weight.